Showing Up, or, Ajay as Accompanist - Boer, Sam (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2025)
Sam Boer reflects on his relationship with Ajay Heble, focusing on his role as an accompanist to activities in the community.